2019
DOI: 10.1097/olq.0000000000000997
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Disease, Human Immunodeficiency Virus, and Pregnancy Testing Behaviors Among Internet and Mobile Dating Application Users and Nonusers, 2016

Abstract: We examined 2016 United States market research to understand the demographics and sexual health testing behaviors of dating app users. Internet/app users were more likely to be young adults, male, nonwhite, of Hispanic ethnicity, and unmarried. Users also reported greater testing for sexually transmitted disease, human immunodeficiency virus, and pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This is reflective of Australian youth, a survey of 1,168 Australian students found that 89% were heterosexual [ 28 ]. Dating app use is also most prevalent in the 18–24-year-old age group [ 29 ] and 90.2% of our survey respondents were in the 18–24-year-old age bracket.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…This is reflective of Australian youth, a survey of 1,168 Australian students found that 89% were heterosexual [ 28 ]. Dating app use is also most prevalent in the 18–24-year-old age group [ 29 ] and 90.2% of our survey respondents were in the 18–24-year-old age bracket.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…For example, nowadays, dating applications help in potential matchmaking that can lead to long relationships like marriage [ [26] , [27] , [28] ]. On the other hand, dating applications can affect one's life in an undesirable way, such as sexual harassment and bullying [ [29] , [30] , [31] ] and vulnerability to sexually transmitted diseases [ 32 , 33 ]. Understanding user motivations can paint a clear picture of the positive and negative outcomes of Bumble usage.…”
Section: Introductionmentioning
confidence: 99%
“…The sample of Italian app users should report engaging in more risky sexual behaviors (with higher numbers of sexual partners of full protected and unprotected sexual intercourse; casual sex encounters, with a higher frequency of “hook-ups”) than former users and non-users. 6 , 7 , 8 , 13 , 17 , 18 , 19 , 20 The sample of Italian app users should also show higher rates of STIs than former users and non-users. 6 , 7 , 8 , 13 , 17 , 18 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 , 8 , 13 , 17 , 18 , 19 , 20 The sample of Italian app users should also show higher rates of STIs than former users and non-users. 6 , 7 , 8 , 13 , 17 , 18 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%